1986
DOI: 10.2337/diab.35.2.172
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Utilization Rates and Insulin Sensitivity In Vivo in Tissues of Virgin and Pregnant Rats

Abstract: In vivo studies have shown that insulin resistance in late pregnancy results from a decreased sensitivity of liver and peripheral tissues. In the present study, measurements of the rates of glucose utilization by skeletal muscles (soleus, extensor digitorum longus, epitrochlearis, and diaphragm), white adipose tissue, and brain of virgin and 19-day pregnant rats were performed in the basal condition and during a euglycemic, hyperinsulinemic (400 microU/ml) clamp to quantify the partition of glucose utilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
66
0
4

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 15 publications
(22 reference statements)
7
66
0
4
Order By: Relevance
“…In vivo studies have shown that pregnant rats become progressively resistant to insulin after day 16 of gestation [5]. In these animals, the insulin resistance of skeletal muscle has been clearly demonstrated in vitro, while the insulin resistance in vivo in peripheral tissues and liver has been substantiated in studies using the euglycaemic-hyperinsulinaemic clamp technique [6,7].Insulin initiates its metabolic and growth-promoting effects by binding to the a subunit of its tetrameric receptor, thereby activating the kinase in the b subunit [8]. This interaction catalyses the intramolecular autophosphorylation of specific tyrosine residues of the b subunit which further enhances the tyrosine kinase activity of the receptor toward other protein substrates [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies have shown that pregnant rats become progressively resistant to insulin after day 16 of gestation [5]. In these animals, the insulin resistance of skeletal muscle has been clearly demonstrated in vitro, while the insulin resistance in vivo in peripheral tissues and liver has been substantiated in studies using the euglycaemic-hyperinsulinaemic clamp technique [6,7].Insulin initiates its metabolic and growth-promoting effects by binding to the a subunit of its tetrameric receptor, thereby activating the kinase in the b subunit [8]. This interaction catalyses the intramolecular autophosphorylation of specific tyrosine residues of the b subunit which further enhances the tyrosine kinase activity of the receptor toward other protein substrates [8].…”
mentioning
confidence: 99%
“…
Insulin resistance during pregnancy has been reported both in women and in experimental animals [1][2][3][4][5][6][7], but the mechanism of this resistance remains unclear. In vivo studies have shown that pregnant rats become progressively resistant to insulin after day 16 of gestation [5].
…”
mentioning
confidence: 99%
“…Inadequate compensatory hypersecretion of insulin to counter insulin resistance is critical to the pathology of type 2 diabetes [3]. Pregnancy is a progressive state of maternal insulin resistance [4][5][6] (reviewed in [7]), which in healthy pregnancies is accompanied by reciprocal increases in insulin secretion (see [5,8]). Gestational diabetes occurs in women who secrete insufficient insulin to compensate for lowered in-sulin sensitivity during the third trimester [9] (reviewed in [3]).…”
Section: Introductionmentioning
confidence: 99%
“…The similar relative decline in insulin-and contraction-stimulated glucose transport raises the possibility that pregnancy impairs a distal process that is common to mechanisms whereby each stimulus activates glucose transport. insulin resistance; gestational diabetes; fatigue; glycogen LATE PREGNANCY (gestational days 18 -22 in the rat, third trimester in humans) is characterized by whole body insulin resistance (8,27). Insulin-stimulated glucose disposal by skeletal muscle during a euglycemic-hyperinsulinemic clamp is reduced in pregnant compared with nonpregnant rats (27).…”
mentioning
confidence: 99%
“…insulin resistance; gestational diabetes; fatigue; glycogen LATE PREGNANCY (gestational days 18 -22 in the rat, third trimester in humans) is characterized by whole body insulin resistance (8,27). Insulin-stimulated glucose disposal by skeletal muscle during a euglycemic-hyperinsulinemic clamp is reduced in pregnant compared with nonpregnant rats (27). Insulin resistance is also a normal characteristic of late pregnancy in humans, presumably to ensure adequate availability of maternal nutrients to the fetus during this period of rapid growth (5,25).…”
mentioning
confidence: 99%